PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN INDUSTRIAL DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Pelleng, Benaya; Karamoy, Herman; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
The timeliness of submitting financial reports has an important impact in meeting the needs of stakeholders, as well as reflecting the company's transparency and accountability, however, it appears that there are still many companies that do not submit their financial reports on time. This research aims to examine the influence of profitability, liquidity and company size on the timeliness of submitting financial reports to companies in the industrial sector listed on the Indonesia Stock Exchange during the period 2019 to 2021. The research method used is quantitative research with a purposive sampling technique. The sample obtained from the selection results was 41 companies. The results of the logistic regression analysis show that liquidity has a significant positive influence on the timeliness of submitting financial reports, while profitability and company size do not have a significant influence. These findings provide a better understanding of the factors that influence the timeliness of submitting financial reports in the industrial sector on the Indonesia Stock Exchange.